Peran Mediasi Environmental Concern Dan Perceived Environmental Consumer Pada Hubungan Antara Sikap Skeptis Konsumen Terhadap Iklan Hijau Dan Perilaku Pembelian Produk Hijau - Jati Waskito (Universitas Negeri Padang, 2017)
The purpose of this study is to examine the effect of skeptic attitude directly or through the role of mediation of Environmental Concern (EC) and Perceived Environmental Consumer (PEC) on the behavior of purchasing green products. The survey with questionnaire instrument in 299 Solo residents, using the structural equation model found that skeptic attitude had direct effect on EC and PEC, but did not significantly influence the buying behavior of green products. PEC becomes a full-fledged mediation role in the influence of consumers' skeptic attitudes toward their purchasing behavior of green products, unlike the EC that cannot mediate those relationships.